PENENTUAN PENGGUNAAN LAHAN GAMBUT UNTUK PENINGKATAN EKONOMI MASYARAKAT DI KABUPATEN INDRAGIRI HULU - Yelly Zamaya; Dahlan Tampubolon; Misdawita Misdawita (Jurnal Planologi, 2021)
Sustainable peatland management will have an impact on the welfare of the community as a whole. Rural communities use peatlands as their primary source of income.  This article aims to formulate plants on peatlands to improve the economy of the community Indragiri Hulu Regency. The method used is a combination of field observation data and a participatory geographic information system (GIS-P). The utilization of peatlands is still dominated by oil palm and rubber plants. Peatlands have the potential for high-value and environmentally friendly vegetation, such as gaharu, barley and liberica coffee. The shallower peatlands are suitable for horticultural vegetation such as rice and short-lived vegetables and fruits. Besides, it is reasonable to cultivate wetlands in Indragiri Hulu, such as catfish, catfish, tilapia and tilapia. Through this participatory information system, it is possible to determine the commodities developed in the region.